Comparative diagnostic accuracy of immunoprecipitation versus immunoassay methods for detecting Aspergillus fumigatus‐specific IgG in allergic bronchopulmonary aspergillosis: A systematic review and meta‐analysis - Sehgal, Inderpaul Singh; Dhooria, Sahajal; Prasad, Kuruswamy Thurai; Muthu, Valliappan; Aggarwal, Ashutosh Nath; Agarwal, Ritesh (Mycoses, 2022)
Background The diagnostic accuracy of immunoassays versus immunoprecipitation methods for detecting A.fumigatus‐specific IgG in patients with allergic bronchopulmonary aspergillosis (ABPA) complicating asthma remains unclear. Methods We performed a systematic review to identify studies describing both the methods in the same ABPA subjects. We assessed study quality using the QUADAS‐2 tool. We derived the relative sensitivity and specificity using the HSROC meta‐regression model. We calculated the number‐needed‐to‐test using an immunoassay to detect one additional positive test in ABPA. Results Our search yielded 20 studies (796 ABPA and 929 controls). The studies had a high risk of bias. The summary estimates for sensitivity and specificity of immunoprecipitation methods were 68.6% (95% CI, 48.4–83.5) and 93.8% (95% CI, 83.6–97.8), respectively, while for immunoassays they were 85.2% (95% CI, 73.3–92.3) and 84.6% (95% CI, 76.0–90.5), respectively. The relative sensitivity and specificity of immunoassays compared to immunoprecipitation tests were 1.29 (95% CI, 1.1–1.6) and 0.91 (95% CI, 0.85–0.97), respectively. The automated immunoassays (1.77; 95% CI, 1.1–2.8) had better relative sensitivity than the manual (1.1; 95% CI, 1.02–1.18) assays compared to immunoprecipitation. The relative specificity of manual immunoassays (0.95; 95% CI, 0.91–0.99) was significantly lower, while that of automated (0.88; 95% CI, 0.77–1.0) assays was lower but not statistically different. One additional positive result was detected for every six (95% CI, 5–7) tests performed with immunoassay (versus immunoprecipitation). Conclusion Compared to immunoprecipiation methods, automated immunoassays have higher sensitivity and similar specificity, manual immunoassays have higher sensitivity and lower specificity, while automated immunoassays have higher sensitivity and similar specificity for detecting A.fumigatus‐IgG in patients with ABPA. [www.crd.york.ac.uk/prospero/display_record.php?RecordID=309864].